КƏСІПТІК ОҚЫТУ БАКАЛАВРЛАРЫН ДАЯРЛАУ ЖҮЙЕСІНДЕ ТЕХНОЛОГИЯ ТҮРЛЕРІН ПАЙДАЛАНУ. - Самашова, Г. Е. (Journal of Educational Sciences, 2016)
Научная статья «Использование технологий в системе подготовки бакалавра профессионального обучения» посвящена одной из актуальных тем общества. В данной работе автор рассматривает виды технологий, им сделан обширный анализ основных технологий, которые используются в учебном процессе вуза, также раскрывает роль и значение технологий в подготовке бакалавра профессионального обучения.The Scientific article "Use technology in system of preparing the bachelor of the professional education" is dedicated to one of actual that society. In given work author considers the types technology, him is made extensive analysis main technology, which are used in scholastic process of the high school, also reveals the role and importance technology in preparing the bachelor of theprofessional education.